Candida glabrata Hst1-Rfm1-Sum1 complex evolved to control virulence-related genes - /, / (2022)
C. glabrata is an opportunistic fungal pathogen and the second most common cause of opportunistic fungal infections in humans, that has evolved virulence factors to become a successful pathogen: strong resistance to oxidative stress, capable to adhere and form biofilms in human epithelial cells as well as to abiotic surfaces and high resistance to xenobiotics. Hst1 (a NAD(+)-dependent histone deacetylase), Sum1 (putative DNA binding protein) and Rfm1 (connector protein) form a complex (HRS-C) and control the resistance to oxidative stress, to xenobiotics (the antifungal fluconazole), and adherence to epithelial cells. Hst1 is functionally conserved within the Saccharomycetaceae family, Rfm1 shows a close phylogenetic relation within the Saccharomycetaceae family while Sum1 displays a distant phylogenetic relation with members of the family and is not conserved functionally. CDR1 encodes for an ABC transporter (resistance to fluconazole) negatively controlled by HRS-C, for which its binding site is located within 223 bp upstream from the ATG of CDR1. The absence of Hst1 and Sum1 renders the cells hyper-adherent, possibly due to the overexpression of AED1, EPA1, EPA22 and EPA6, all encoding for adhesins. Finally, in a neutrophil survival assay, HST1 and SUM1, are not required for survival. We propose that Sum1 in the HRS-C diverged functionally to control a set of genes implicated in virulence: adherence, resistance to xenobiotics and oxidative stress.